INFLUENCE MODEL PROBLEM BASED LEARNING (PBL) UNDERSTANDING THE CONCEPT OF BEGINNING OF SCIENCE PROCESS SKILL (KPS) SENIOR HIGH SCHOOL STUDENT - Frikson Jony Purba (Jurnal Pendidikan Fisika, 2015)
This study aimed to determine the effect model of problem-based  learning (PBL) with initial conceptual understanding of the science process skills of students on the material Waves and Sound. This research is a quasi experimental with the entire population of high school students of class XII HKBP Sidorame Medan academic year 2014/2015. The instrument used in this study is to test understanding of concepts in the form of multiplechoice tests and science process skills test in the form of description. Science process skills of observation carried out during the learning process and test understanding of concepts used before the beginning of learning to classify students into groups of high and low understanding of the concept and science process skills test conducted sebelim and after application of learning models. Science process skills test data analyzed by statistical test to test the hypothesis using t-test. Improved science process skills analyzed by normalized gain value, N-gain. The results showed that the model of problem-based learning (PBL) with high initial understanding of the concept of influence on science process skills of students with a significant difference to students with low to the understanding of the concept of matter waves and sound. And the conventional group was not significant differences between the groups pemahamn low and high concept. Application of PBL models can better improve students' science process skills than conventional models and are included in the medium category.